Learning induces coordinated neuronal plasticity of metabolic demands and functional brain networks - Sebastian Klug; Godber M. Godbersen; Lucas Rischka; Wolfgang Wadsak; Verena Pichler; Manfred Klöbl; Marcus Hacker; Rupert Lanzenberger; Andreas Hahn (Communications Biology, 2022)
Brain network analyses reveal coupled changes between functional connectivity and metabolic demands that relate to cognitive performance improvements induced by learning a challenging visuo-spatial task for four weeks.